KERAGAMAN GENETIK Aquilaria malaccensis DARI BANGKA BARAT PROVINSI KEPULAUAN BANGKA BELITUNG DAN IMPLIKASINYA UNTUK PENGELOLAAN TEGAKAN BENIH - I. L. G. Nurtjahjaningsih; AYPBC Widyatmoko; Liliek Haryjanto; Yuliah Yuliah; Yayan Hadiyan (Jurnal Pemuliaan Tanaman Hutan, 2020)
Aquilaria malaccensis (agarwood) is a native species to Indonesia, it produces fragrance. Aim in this study was to assess genetic diversity and structure of A. malaccensis in order to manage seed stand to produce high quality and quantity seeds/seedlings. Leaf samples for DNA template were collected from  populations at western Bangka i.e. Air Gantang, Pelangas, and Simpang Gong. Amplifications of 14 RAPD markers were confirmed; 42 DNA samples of A. malaccensis were analysed using RAPD markers. Parameters of genetic diversity within population i.e. private alleles (PA) and expected heterozygosity (H) were calculated using GeneAlex software. Genetic structure among populations were determined as genetic distance (Da), Analysis Molecular of Variance (AMOVA), a neighbor-joining tree, were calculated using GeneAlex and PopTrew software. Eleven out of 14 RAPD markers were produced 104 stable and polymorphic alleles; PE were found at Air Gantang and Pelangas, 1 and 2 alleles, respectively. The H ranged between 0.133 (Simpang Gong) and 0.328 (Pelangas). The Da was moderate (0.099). AMOVA showed significant genetic diversity among populations (14%). A neighbor-joining tree showed the populations divided into two clusters with high boostrap value, and concordance with their geographical positions. Restricted gene flow might cause a high genetic relationship among populations. Low HEE in Simpang Gong caused this population was priored to being conserved; Air Gantang and Pelangas should be designed as different conservation units due to the population contained different private alleles.